GHI Launch Des Moines 2012 - Catley-Carlson, Margaret (2012)
2012 Global Hunger Index Launch Event "The Challenge of Hunger: Ensuring Sustainable Food Security Under Land, Water & Energy Stresses" with Margaret Catley-Carlson (World Economic Forum Advisory Council on Water) October 18, 2012